2014
DOI: 10.12809/hkmj134074
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intimate partner violence against women in a mega city of South-Asia: multi-centre cross-sectional study

Abstract: Objectives:To assess the proportion of women subjected to intimate partner violence and the associated factors, and to identify the attitudes of women towards the use of violence by their husbands.Design: Cross-sectional study. Setting:Family practice clinics at a teaching hospital in Karachi, Pakistan.Participants: A total of 520 women aged between 16 and 60 years were consecutively approached to participate in the study and interviewed by trained data collectors. Overall, 401 completed questionnaires were av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
(36 reference statements)
10
17
0
1
Order By: Relevance
“…is result (37.5%) is in line with findings from Pakistan (35%) [22] and Nigeria (34.3%) [23] and a study in Ethiopia, Jimma 35.6% [19]. But this is lower as compared to the studies carried out in Zimbabwe (63.1%) [24], Uganda (48%) [25], South Africa (44%) [26], Mozambique (44%) [27], and Kenya (66.9%) [28] and the studies conducted in Ethiopia, Abay Chamo (44.5%) [11] and Gonder (58.7%) [8].…”
Section: Discussionsupporting
confidence: 89%
“…is result (37.5%) is in line with findings from Pakistan (35%) [22] and Nigeria (34.3%) [23] and a study in Ethiopia, Jimma 35.6% [19]. But this is lower as compared to the studies carried out in Zimbabwe (63.1%) [24], Uganda (48%) [25], South Africa (44%) [26], Mozambique (44%) [27], and Kenya (66.9%) [28] and the studies conducted in Ethiopia, Abay Chamo (44.5%) [11] and Gonder (58.7%) [8].…”
Section: Discussionsupporting
confidence: 89%
“…7 Various risk factors have been identified as relating to the occurrence of violence against women, including sociodemographic and socioeconomic characteristics, substance use, and history of having witnessed family violence in infancy or adolescence. 5,9 These facts demonstrate that violence against women is multi-faceted and, under a socioecological perspective, is the product of complex interactions between individuals, families, communities, and social level factors. 10 RESUMO: Objetivo: Descrever o perfil da violência contra mulheres em diferentes ciclos de vida, de acordo com as características sociodemográficas das vítimas e dos agressores.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the sociological theories show that low levels of education, socioeconomic condition, stress, lack of support from authorities (health services and social well-being), and a closed social network contribute to a larger occurrence of intimate partner violence. 9 The exposition of violence perpetrated by a partner may can bring up feelings of hatred and disaffection toward him. In tense situations, women tend to report symptoms of headaches, depression, and other mental disorders, like suicide attempts.…”
mentioning
confidence: 99%
“…According to study results of World Health Organization 2002, domestic violence rate was reported as 10-69% by their spouses or partners (2). Although the rates change from country to country, exposure rate of life-long violence for women in the literature have been reported as 38.6% in Nepal, 41% in India, 35% in Pakistan, and 23.8% in the United Kingdom (3)(4)(5)(6). In a study conducted on 24048 married women in 2009 in our country by Family and Social Policy Ministry, it was determined that physical violence rate was 39%, sexual violence rate was 15%, emotional violence rate was 44%, and economical violence rate was 23% (7).…”
Section: Introductionmentioning
confidence: 99%